Narrative Unreliability in Paula Hawkins’ The Girl on the Train as a Strategy of Reader Immersion - Grebeniuk, T.; Гребенюк, Тетяна Володимирівна (My University, 2018)
This paper considers thea narratological phenomenon of unreliable narration in the novel The Girl on the Train by Paula Hawkins, concentrating on mechanisms of the reader’s perception of it. Starting with a survey of the main contemporary definitions of unreliable narration and theas well as sources of unreliability, the article moves to the problem of how the unreliable narration can influences on the Hawkins’ novel a reader of the analysed text, discussing the ways in which unreliabilityit combines with the other aspects of the narrative functioning. The influence effect of unreliable narration on the reader is analyzed examined in terms of recipient’s immersion to the narrative. The dDisclosure of an unreliableility factstatments, the search of thefor truth hidden under beneath the cover of narration, along with observation of the regainrecuperation of the “reliability” of the narrator’s “reliability” are viewed as supplementary objects of the reader’s interest during the text perception. The aAttention in the article is focused on two components of the reader’s gratification as manifest in Hawkins’ novel: intellectual satisfaction due to the solution of the murder mystery solution (in the sphere of temporal immersion), and emotionalas well as satisfaction due toresulting from the protagonist’s psychic recovery and revenge (in the sphere of emotional immersion). The last section of the paper compares the reader’s perception of the novel with the viewer’s reactions to the Tate Taylor’s a screen version directed by Tate Taylorof it.
Keywords: unreliable narrator; narrative; the reader; immersion; sources of unreliability